Calcification of the Olfactory Bulbs in Three Patients with Hyposmia - Ishman, Stacey L.; Loehrl, Todd A.; Smith, Michelle M. (American Journal of Neuroradiology, 2003)
Summary: An estimated two million Americans suffer from chemosensory disorders. We present the clinical and imaging findings in three hyposmic patients with bilateral olfactory bulb calcification detected by CT. To our knowledge, these are the first cases of olfactory bulb calcification reported in the literature. A review of the literature concerning calcification of cranial nerves, olfactory neuritis, and the potential etiology and clinical significance of olfactory bulb calcification in our patients is presented.